The Institutional Regulatory Environment of the Digital Ecosystem: Theoretical Approach and Russian Experience - Masyuk Natalya; Bushueva Marina; Bragina Zinaida (SHS Web of Conferences, 2020)
Digitalization is an integral part of global change in the world economy. The successful creation and functioning of a digital economy are possible only in an adequate digital ecosystem. The main criterion for the formation of a digital ecosystem is the maturity and stability of its institutional environment, including the totality of new institutions. The creation of digital institutions is a new phenomenon of institutionalization and accompanies the introduction of digital technologies in the digital ecosystem. The article defines the concept of institutionalization in connection with the analysis of the economic interests of business entities operating in the regions of Russia. The definition of digital institutions as new social institutions in the digital age is formulated. The structure and basic elements of the institutional regulatory environment of the digital ecosystem that is necessary for regulating digital transformations in the digital ecosystem are determined.